Oncology Reviews: reasons for a new oncology journal - Camillo Porta (Frontiers Media S.A., 2011)
A year ago, when we started considering the possibility of creating a new oncology journal, our first question was to ask if there was a real need for yet another periodical in the crowded panorama of oncology...